Peran Audit Operasional dalam Meningkatkan Efisiensi dan Akuntabilitas Dana BPOPP di SMK NU 1 Babat - Tiara Eka Putri; Intan Ayu; Thoifatul Munawaroh; Fitria Novita Sari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Operational audits play an important role in ensuring the efficiency and accountability of education fund management This study aims to analyze the role of operational audits in enhancing the efficiency and accountability of BPOPP fund management at SMK NU 1 Babat. A qualitative case study approach was employed through in-depth interviews, direct observations, and document analysis. The findings reveal that BPOPP fund management has been carried out effectively, starting with collaborative budget planning through RKAS formulation. Fund implementation aligns with the planned budget, although delays in disbursement occasionally occur and are managed through alternative funding. Accountability is maintained through regular reporting with comprehensive supporting documentation, and transparency is upheld through the involvement of the school foundation and communication with parents. Operational audits play a critical role in evaluating the management system, identifying weaknesses, and providing recommendations for improvement.